The relationship between work-life balance programs and affective commitment among rank & files employees of Usima Group of Companies Sdn. Bhd / Nurulaini Ibrahim - Ibrahim, Nurulaini (2014)
The purpose of this study was to identify the relationship between work-life balance programs and affective commitment among rank & files employees. The conceptual framework for this study was based on model of Lazarova (2004) shown in Chapter 2, Figure 2.1. In the beginning of this study, convenience sampling was used as the sampling technique. The respondents are rank & files employees from the ones of private company in Kedah. The study generated 100 % response rate from 100 respondents. The result shows that work life balance programs have significant relationship towards affective commitment.